Bacterial community analysis in the rice straw sample before and after composting by PCR-DGGE and cloning method - Duc Duy, Ngo; Hoang Dung, Nguyen; Quoc Khanh, Hoang (Vietnam Journal of Biotechnology, 2020)
Applicability of PCR-DGGE (Polymerase Chain Reaction-Denaturing Gel Gradient Eletrophoresis) technique to analyze microbial community is based on the V3 gene fragments in the rice straw sample (R) and after composting rice straw samples (Rn). Besides clonning method combined with analyzing Rn samples and comparing the results of microbial community analysis with PCR-DGGE method had the same reuslts is the main goal in this study. Results obtained from PCR-DGGE technique of R sample had 5 the V3 gene fragments (R1, R2, R3, R4 and R5) and Rn had 4 the V3 genes fragments (Rn1, Rn2, Rn3 and Rn4). Comparison of bacterial groups in R and Rn samples showed that bacteria in R samples including Agrobacterium, Clostridium, Bacteroidetes, Thermopolysporasa and Bacillus species, but in the Rn sample after incubation, the remaining bacterial results of 2 main species are Agrobacterium and Clostridium. Using Clonning method of Rn sample also gave 4 positions and gene fragment sizes corresponding to the positions of Rn1, Rn2, Rn3 and Rn4 from representatives of about 30 samples collected from the Clonning products. Based on the comparison of the similarity among the sequence of V3 gene fragments in PCR-DGGE and Clonning with reference to the data base in NCBI gene bank the results that Rn1 and Rn4 genes are similar to Agrobacterium species, about 96%, Rn2 and Rn3 are similar to Clostridium about 99%. In summary the results of microbial community analysis in the R sample show that the diversity of bacteria in the R sample is larger than in the Rn sample. Summarize the results of microbial community analysis in the R sample show the diversity of bacteria but less stable than the Rn sample. In addition, cloning and PCR-DGGE produced similar results on the sample Rn.